2015
DOI: 10.1007/s10544-015-9964-7
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of circulating tumor cells in tumor-bearing mouse blood by a deterministic lateral displacement microfluidic device

Abstract: Concentration of real tumor cells leaking into blood from cancer was attempted by a deterministic lateral displacement (DLD) microfluidic device. Spiked cultured cell line tumor cells are often used to verify performance of the circulating tumor cells (CTCs) separation methods. Cultured tumor cells are obviously larger than most of hematocytes and considered not to be appropriate as CTC mimics, while there is uncertainty in identifying real CTCs from clinical samples and there is no practical way to examine CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 27 publications
1
41
0
Order By: Relevance
“…8) On the other hand, it has been reported that non-adherent abnormal CTCs can be detected based on the expression of tumor antigens and biophysical deformities. 9,[11][12][13][14][15][16][17][18] The positive expression of CTC protein markers such as cytokeratin -8, -18 and -19, CD44 and the epithelial cell adhesion molecule (EpCAM) is often found in a CTC. 10) To date, the CellSearch system (Veridex, LLC, USA), which is based on immunostaining for CKs + , CD45 -and nucleus + , is the only device that is currently approved by the Food and Drug Administration for CTC detection,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8) On the other hand, it has been reported that non-adherent abnormal CTCs can be detected based on the expression of tumor antigens and biophysical deformities. 9,[11][12][13][14][15][16][17][18] The positive expression of CTC protein markers such as cytokeratin -8, -18 and -19, CD44 and the epithelial cell adhesion molecule (EpCAM) is often found in a CTC. 10) To date, the CellSearch system (Veridex, LLC, USA), which is based on immunostaining for CKs + , CD45 -and nucleus + , is the only device that is currently approved by the Food and Drug Administration for CTC detection,.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] The capture, isolation and enrichment of non-adherent abnormal CTC are based on their difference from hematologic cells in size and biophysical deformities such as such as shape, stiffness and electrical polarizability. [13][14][15][16][17][18][25][26][27][28][29] Many studies have reported that tumor cells are larger in size as compared to hematologic cells and this difference accounts for the…”
Section: Introductionmentioning
confidence: 99%
“…Larger size cells will move laterally toward to the side of channel; smaller particles will flow along the original trajectory. [61][62][63][64][65] DLD arrays allow continuous cancer cell enrichment from peripheral blood. However, the cancer cell purity was still very low after enrichment.…”
Section: Hydrodynamicsmentioning
confidence: 99%
“…Deterministic lateral displacement (DLD) is a method of particle separation, based on the continuous flow of particles through an array of obstacles that exhibits exceptional resolution in size-based separations. 3 DLD has been used for cell and bioparticle separations such as blood fractionation, 4-8 trypanosome enrichment from blood, 9,10 cancer cell isolation [11][12][13] and CTC cell cluster isolation from whole blood, 14 DNA and exosome separation, 15 and the separation of cells based on parameters other than size, namely shape and deformability, 16,17 and dielectric properties. 18 Early theoretical work by Inglis et al 19 and Davis et al 20 describing the critical size in DLD arrays has been improved upon by studying the effects of post shape.…”
Section: Introductionmentioning
confidence: 99%